The Difference Of Social Status Reflected In Charles Dickens' A Christmas Carol Novel (1843): A Marxist Approach - Oktaviana, Lia; , Drs. Abdillah Nugroho, M. Hum; , Mauly Halwat Hikmat, Ph. D (2014)
The major problem of this study is to reveal how the difference of social status is reflected in A Christmas Carol novel. The study focuses on the difference of social status. The objective of this study is to analyze the novel based on its structural elements and a marxist approach. In analysis, the researcher uses qualitative method. The object of the study is A Christmas Carol novel written by Charles Dickens. The data sources consist of primary and secondary data sources. The primary data source is A Christmas Carol novel itself and the secondary data sources are the other sources related to the primary data such as the information about author's biography, information of England country, and the other relevant information to analyze of this research. The method of the data collection are reading the novel, browsing to the internet, indentifying the problem and the finding the data, taking notes the important data, arranging the data based on category of elements of literature review, and the last is drawing conclusion and suggestion based on the analysis of the data. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusion and suggestion. First, Charles Dickens wants to describe that miserly people, do not care with the poor and worship to money. Second, based on marxist analysis, Charles Dickens wants to reflect that the difference of social status that happens in a society is not problem because Christmas day is a happy day.